The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/aic.13944
|View full text |Cite
|
Sign up to set email alerts
|

Bubble columns for condensation at high concentrations of noncondensable gas: Heat‐transfer model and experiments

Abstract: Carrier gas based thermodynamic cycles are common in water desalination applications.These cycles often require condensation of water vapor out of the carrier gas stream. Since the carrier gas is most likely a non-condensable gas present in very high concentrations (60-95%), a large additional resistance to heat transfer is present. We propose to reduce the aforementioned thermal resistance by condensing the vapor-gas mixture in a column of cold liquid rather than on a cold surface by using a bubble column hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 53 publications
4
54
1
Order By: Relevance
“…Dehumidification in bubble columns has previously been shown to reduce device volume and condenser area by an order of magnitude [5]. A schematic diagram of the bubble column dehumidifier used in this work is shown in However, the key advantage of the bubble column dehumidifier lies in moving the condensation process off an expensive solid surface and onto the surface of a swarm of bubbles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dehumidification in bubble columns has previously been shown to reduce device volume and condenser area by an order of magnitude [5]. A schematic diagram of the bubble column dehumidifier used in this work is shown in However, the key advantage of the bubble column dehumidifier lies in moving the condensation process off an expensive solid surface and onto the surface of a swarm of bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, practical bubble column dehumidifiers for HDH desalination need to be very short to ensure a minimal gas-side pressure drop, and several researchers have noted that the gas and liquid phases behave differently near the gas inlet [10,11,12,13]. Most bubble column reactors are significantly taller than those used for dehumidification [5,10], so the entry region is often neglected in the reactor modeling and design literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a short bubble column for dehumidification was first introduced by Narayan et al [6] and was found to be very promising since it reduces the negative effect of the noncondensable gases on condensation. In traditional dehumidification systems, water vapor has to diffuse through an air layer, which increases the resistance to the mass transfer.…”
Section: Bubble Column Dehumidifiermentioning
confidence: 99%
“…In traditional dehumidification systems, water vapor has to diffuse through an air layer, which increases the resistance to the mass transfer. In a bubble column, the location of condensation is the transiently formed bubble-water interface which has a very large specific area, giving it superior efficiency compared to alternative dehumidification systems [6,7].…”
Section: Bubble Column Dehumidifiermentioning
confidence: 99%